Implementasi Teorema Bayes Dalam Diagnosa Penyakit Ayam Broiler - Nasyuha, Asyahri Hadi; Hafizah, Hafizah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Broiler chickens are a type of chicken produced from the cultivation of animal husbandry technology which has a characteristic of fast growth, as a meat producer with low feed conversion and is ready to slaughter at the age of 28-45 days. Chicken health affects the benefits that will be obtained by the farmer, therefore the Expert System for diagnosing chicken disease using the Bayes Theorem method was developed to help users, especially broiler chicken breeders, in diagnosing diseases along with suggestions or recommended countermeasures. The application of the Bayes Theorem method in diagnosing disease in broilers is by entering the calculation algorithm of the Bayes Theorem method into the system, so that the expert system can perform calculations using the Bayes Theorem method and provide diagnostic results and correct solutions to the specified disease.